Case study in CSP plant performance. Issue 2 (March 2015) - Wright, Christopher Ian
Abstract : USING ROUTINE sampling and chemical analysis of heat transfer fluid, early in a plant build, can help to extend the lifetime of CSP plants. Christopher Ian Wright BSc PhD MBA, explains.